RELATIONSHIP INITIATION BREAKING IN EARLY AND AGE OF EXTENSION WITH NUTRITIONAL STATUS CHILDREN AGE 6-24 MONTHS IN THE AREA BLAHBATUH II PUSKESMAS WORK GIANYAR - Putu Mira Aryanti; I.G.A Ari Widarti; Desak Putu Sukraniti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Nutritional status is a measure of success in fulfilling nutrition for children which is indicated by the child's weight and height. Nutritional status is also defined as the health status produced by a balance between nutritional needs and inputs. Indirect factors that influence nutritional status include breastfeeding initiation, and age of weaning. The purpose of this study was to determine the relationship of initiation of early breastfeeding and weaning age with nutritional status of children aged 6-24 months in the work area of the blahbatuh II health center in Gianyar. The type of research conducted was observational with a cross sectional design. The sample size in this study was 99 people. Data collection was carried out interview using questionnaires initiating early breastfeeding, weaning age and sample identity. Data was processed by statistical analysis of Rank Sperman correlation. The results of this study showed that initiating early breastfeeding was (52.2%) with good nutritional status, and children with more nutritional status (2%) whereas those who did not initiate early breastfeeding were (7.1%) with poor nutritional status, and children with good nutritional status of (47.8%). Those who did weaning at 24 months of age were (21.2%) with poor nutritional status, while those who did weaning at ≥ 24 months of age were (76.8%) with good nutritional status, and with more nutritional status (2, 0%). Those who did IMD for weaning age ≥ 24 months were (78.8%) while those who did not have IMD 24 months weaning age were (21.2%). There is a relationship between the initiation of early breastfeeding and the nutritional status of p = 0.001 (p 0.05). There is a relationship between weaning age and nutritional status p = 0.008 (p 0.05). There is a relationship between IMD and weaning age value p = 0.000 (p 0.05). Keywords: IMD, Age of Weaning, Nutritional Status, Children Aged 6-24 Months